2003
DOI: 10.1248/cpb.51.590
|View full text |Cite
|
Sign up to set email alerts
|

A Novel ent-Kaurane Diterpenoid from the Croton tonkinensis GAGNEP

Abstract: Croton tonkinensis GAGNEP belonging to Euphobiaceae grows wildly in Vietnam, and the leaves of this plant are prescribed for stomachache. 1) The crude drug from the leaves was previously shown to have an inhibitory effect on malaria parasites. 2) Later, Phan et al. 3) reported the isolation and structural elucidation of a new ent-kaurane diterpenoid, ent7b-hydroxy-15-oxokaur-16-en-18-yl acetate from the leaves. In the course of our investigation of the biologically active compounds from Vietnamese medicinal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 3 publications
(1 reference statement)
0
15
0
Order By: Relevance
“…3 C. tonkinensis, a species native in Vietnam, has been a prolific source of ent-kauranetype diterpenoids. From leaves of this species ent-7β-hydroxy-15-oxokaur-16-en-18-yl acetate 63 and ent-1α-acetoxy-7β,14α-dihydroxy-kaur-16-en-15-one 64 45 although it may be found also in the leaf chloroplasts of C. stellatopilosus Ohba. 67 C. oblongifolius has been a prolific source of diterpenoids, including: (i) the clerodane 11-dehydro (-) hardwickiic acid; 68 (ii) the labdanes labda-7,12(E),14-triene, labda-7,12(E),14-triene-17-al, labda-7,12(E),14-triene-17-ol, labda-7,12(E),14-triene-17-oic acid; 69 (iii) the cembranoid diterpenes crotocembranoic acid and neocrotocembranal 70 (6); (iv) the cytotoxic labdane diterpenoids 2-acetoxy-3-hydroxy-labda-8(17),12(E)-14-triene, 3-acetoxy-2-hydroxy-labda-8(17),12(E)-14-triene, and 2,3-dihydroxy-labda-8(17),12(E),14-triene were also isolated from the stem bark of C. oblongifolius; 71 (v) the labdane nidorellol, the furoclerodane croblongifolin and the clerodane crovatin; 72 (vi) the kaurane (-)ent-kaur-16-en-19-oic acid; 40 (vii) the halimanes crotohalimaneic acid (7), crotohalimoneic acid and 12-benzoyloxycrotohalimaneic acid; 73 (viii) new labdane-type diterpenoids 3-oxygenated ent-manoyl oxide derivatives with a 8,13-epoxytricyclic ring system and hydroxylabdandienes.…”
Section: Diterpenesmentioning
confidence: 90%
“…3 C. tonkinensis, a species native in Vietnam, has been a prolific source of ent-kauranetype diterpenoids. From leaves of this species ent-7β-hydroxy-15-oxokaur-16-en-18-yl acetate 63 and ent-1α-acetoxy-7β,14α-dihydroxy-kaur-16-en-15-one 64 45 although it may be found also in the leaf chloroplasts of C. stellatopilosus Ohba. 67 C. oblongifolius has been a prolific source of diterpenoids, including: (i) the clerodane 11-dehydro (-) hardwickiic acid; 68 (ii) the labdanes labda-7,12(E),14-triene, labda-7,12(E),14-triene-17-al, labda-7,12(E),14-triene-17-ol, labda-7,12(E),14-triene-17-oic acid; 69 (iii) the cembranoid diterpenes crotocembranoic acid and neocrotocembranal 70 (6); (iv) the cytotoxic labdane diterpenoids 2-acetoxy-3-hydroxy-labda-8(17),12(E)-14-triene, 3-acetoxy-2-hydroxy-labda-8(17),12(E)-14-triene, and 2,3-dihydroxy-labda-8(17),12(E),14-triene were also isolated from the stem bark of C. oblongifolius; 71 (v) the labdane nidorellol, the furoclerodane croblongifolin and the clerodane crovatin; 72 (vi) the kaurane (-)ent-kaur-16-en-19-oic acid; 40 (vii) the halimanes crotohalimaneic acid (7), crotohalimoneic acid and 12-benzoyloxycrotohalimaneic acid; 73 (viii) new labdane-type diterpenoids 3-oxygenated ent-manoyl oxide derivatives with a 8,13-epoxytricyclic ring system and hydroxylabdandienes.…”
Section: Diterpenesmentioning
confidence: 90%
“…Its leaves have been used to treat burns (boils), abscesses, impetigo, abdominal pain, dyspepsia, gastric and duodenal ulcers [2], stomachache as well as to cure malaria paradise, urticarial, leprosy, psoriasis and genital organ prolapse [1][2][3][4]. Phytochemical investigations on C. tonkinensis have shown the presence of benzoic acid, sterols, long-chain alkyl alcohols, flavonoid glucosides [5] and ent-kaurane diterpenoids [6][7][8][9][10][11][12][13]. Recently, several studies revealed that the presence of ent-kaurane diterpenoids was correlated to toxicity [11] anti-inflammatory and cancel chemo-preventive activities [9,16], which prompted us to continuously investigate the antioxidant potential of these phytochemical constituents.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the CH bond dissociation enthalpies (BDEs) of seven ent-kaurane diterpenoids extracted from Croton tonkinensis Gagnep including: ent-18-acetoxy-7hydroxykaur-16-en-15-one (1) [15,16], ent-1α-acetoxy-7,14α-dihydroxykaur-16-en-15-one (2) [7,9], ent-16(S)-18-acetoxy-7-hydroxykaur-15-one (3) [10,16], ent-7,14α-dihydroxykaur-16en-15-one (4) [9,17], ent-18α-acetoxy-7α,14-dihydroxykaur-16-en-15-one (5) [9], ent-1α,14αdiacetoxy-7-hydroxykaur-16-en-15-one (6) [10], ent-1α,7-diacetoxy-14α-hydroxykaur-16-en-15-one (7) [10] compounds ( Figure 1) are systematically calculated at M05-2X/6-31+G(d) level of theory in order to evaluated the antioxidant potential via hydrogen atom transfer (HAT) mechanism. In addition, the effects of different substituents such as -NH 2 , -OH, -NO 2 , -SH, -CN, -Cl, -CONH 2 , -CH-(CH 3 ) 2 , -NHCOCH 3 , -OCOCH 3 and -C 2 H 5 on BDE values will be investigated in the attempt to ameliorate their antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used commonly in traditional prescription to treat leprosy, psoriasis, malaria, and genital organ prolapse . E nt‐ kaurane‐type diterpenoids were isolated from the leaves of Croton tonkinensis Gagnep, and their structure determined from phytochemical investigations . For some of them, the cytotoxic properties have been tested against breast MCF‐7, lung A549 , liver SK‐HEP1 , intestinal CaCo‐2, and colon LS180 cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%